Trans-Cinnamaldehyde, Eugenol and Carvacrol Reduce Campylobacter jejuni Biofilms and Modulate Expression of Select Genes and Proteins - Wagle, Basanta R.; Upadhyay, Abhinav; Upadhyaya, Indu; Shrestha, Sandip; Arsi, Komala; Liyanage, Rohana; Venkitanarayanan, Kumar; Donoghue, Dan J.; Donoghue, Annie M. (Frontiers in Microbiology, 2019)
Campylobacter jejuni is the leading cause of human foodborne illness globally, and is strongly linked with the consumption of contaminated poultry products. Several studies have shown that C. jejuni can form sanitizer tolerant biofilm leading to product contamination, however, limited research has been conducted to develop effective control strategies against C. jejuni biofilms. This study investigated the efficacy of three generally recognized as safe status phytochemicals namely, trans-cinnamaldehyde (TC), eugenol (EG) or carvacrol (CR) in inhibiting C. jejuni biofilm formation and inactivating mature biofilm on common food contact surfaces at 20 and 37°C. In addition, the effect of phytochemicals on biofilm architecture and expression of genes and proteins essential for biofilm formation was evaluated. For the inhibition study, C. jejuni was allowed to form biofilms either in the presence or absence of sub-inhibitory concentrations of TC (0.75 mM), EG (0.61 mM) or CR (0.13 mM) for 48 h and the biofilm formation was quantified at 24-h interval. For the inactivation study, C. jejuni biofilms developed at 20 or 37°C for 48 h were exposed to the phytochemicals for 1, 5, or 10 min and surviving C. jejuni in the biofilm were enumerated. All phytochemicals reduced C. jejuni biofilm formation as well as inactivated mature biofilm on polystyrene and steel surface at both temperatures (P<0.05). The highest dose of TC (75.64 mM), EG (60.9 mM) and CR (66.56 mM) inactivated (>7 log reduction) biofilm developed on steel (20°C) within 5 min. The genes encoding for motility systems (flaA, flaB, flgA) were downregulated by all phytochemicals (P<0.05). The expression of stress response (cosR, ahpC) and cell surface modifying genes (waaF) was reduced by EG. LC-MS/MS based proteomic analysis revealed that TC, EG, and CR significantly downregulated the expression of NapA protein required for oxidative stress response. The expression of chaperone protein DnaK and bacterioferritin required for biofilm formation was reduced by TC and CR. Scanning electron microscopy revealed disruption of biofilm architecture and loss of extracellular polymeric substances after treatment. Results suggest that TC, EG, and CR could be used as a natural disinfectant for controlling C. jejuni biofilms in processing areas.